Perbandingan Hukum Pertanggungjawaban Pidana Korporasi Tentang Perlindungan Dan Pengelolaan Lingkungan Hidup : Analisis Antara Amerika Dan Indonesia - Rozeli, Rozeli; Susila, Endrio (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2024)
Introduction: The large amount of pollution and environmental damage is caused by large-scale exploitation of nature, both sea, land, and air. Therefore, it is necessary to realize the principles of laws and regulations on environmental protection and management. Purposes of the Research: For corporate criminal liability based on the Law on Environmental Protection and Management and comparing the compensation lawsuit system in the United States and Indonesia. Methods of the Research: The method in this study is Normative Juridical Law, using the approach of the Law, in the form of literary books, journals, articles with research objects. Results Originality of the Research: Based on the results of the study, the existence of corporations as legal subjects can be held criminally liable as, the Direct Liability theory, a corporation can be burdened with criminal liability, while in the Vicarious Liability Theory, liability is imposed on the corporation or the person in charge of the business can be held criminally liable.